2018
DOI: 10.1007/s10856-018-6088-7
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid hydrogels incorporating platelet lysate enhance human pulp cell proliferation and differentiation

Abstract: The restoration of dentine-pulp complex remains a challenge for dentists; nonetheless, it has been poorly addressed. An ideal system should modulate the host response, as well as enable the recruitment, proliferation and differentiation of relevant progenitor cells. Herein was proposed a photocrosslinkable hydrogel system based on hyaluronic acid (HA) and platelet lysate (PL). PL is a cocktail of growth factors (GFs) and cytokines involved in wound healing orchestration, obtained by the cryogenic processing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 53 publications
7
44
0
Order By: Relevance
“…Human dental pulp cells (hDPCs) were isolated from human third molars under the scope of a previous study [29]. These cells were positive for mesenchymal stem cell markers such as CD73, CD90, CD105 and CD44 with over 98% of cells expressing these markers, and negative for the hematopoietic markers CD34 and CD45 (<1%) [29].…”
Section: Expansion Of Human Dental Pulp Cells (Hdpcs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Human dental pulp cells (hDPCs) were isolated from human third molars under the scope of a previous study [29]. These cells were positive for mesenchymal stem cell markers such as CD73, CD90, CD105 and CD44 with over 98% of cells expressing these markers, and negative for the hematopoietic markers CD34 and CD45 (<1%) [29].…”
Section: Expansion Of Human Dental Pulp Cells (Hdpcs)mentioning
confidence: 99%
“…Human dental pulp cells (hDPCs) were isolated from human third molars under the scope of a previous study [29]. These cells were positive for mesenchymal stem cell markers such as CD73, CD90, CD105 and CD44 with over 98% of cells expressing these markers, and negative for the hematopoietic markers CD34 and CD45 (<1%) [29]. hDPCs were cultured in 75 cm 3 flasks with Dulbecco's Modified Eagle's Medium -low glucose (DMEM, Sigma-Aldrich, USA) and supplemented with 10% fetal bovine serum (FBS, Life Technologies, USA), and 1% antibiotic/antimycotic (Life Technologies, USA).…”
Section: Expansion Of Human Dental Pulp Cells (Hdpcs)mentioning
confidence: 99%
“…However, two main problems remain: high degradability rate and low mechanical properties. Combination of PL in a hydrogel can protect growth factors and biomolecules from degradation and allow their continuous release [47]. Babo PS et al incorporated PL into HA hydrogels which resulted in sustained release of growth factors and enhanced the viability of cells either encapsulated in or seeded within the hydrogels [76,77].Our results revealed that addition of PL increased the Young's modulus as well as the viscoelastic modulus (G', G") of alginate hydrogel.…”
Section: Discussionmentioning
confidence: 57%
“…The viability of hBM-MSCs encapsulated in Alg-based hydrogels was assessed. Previous studies have demonstrated the positive effect of PL upon the viability and proliferation of hBM-MSCs in combination with other hydrogels such as hyaluronic acid [47], gellan gum gels [85], coating the scaffolds [86] and even used alone as a hydrogel [50]. In addition, it has been shown that incorporation of CS into the network supports the viability and proliferation of chondrocytes for at least six weeks [87].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation